Role of liposomal amphotericin B in intensive care unit: an expert opinion paper - Linda Bussini; Michele Bartoletti; Matteo Bassetti; Andrea Cortegiani; Gennaro De Pascale; Francesco Giuseppe De Rosa; Marco Falcone; Maddalena Giannella; Massimo Girardis; Paolo Grossi; Malgorzata Mikulska; Paolo Navalesi; et al. (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Introduction Invasive fungal infections (IFI) are frequent in patients admitted to the intensive care unit (ICU). The use of first-line antifungals like triazoles or echinocandins may be limited by the global spread of multi-drug resistance species, drug–drug interactions, low organ penetration, and some safety concerns in case of multi-organ failure. Liposomal amphotericin B (L-AmB) is a polyene drug with a broad activity against mold and yeast and an acceptable safety profile. To outline the role of L-AmB in the treatment of IFI in critically ill patients, a panel of experts was invited to draw up an expert opinion paper on the appropriate place in therapy of L-AmB in different clinical scenarios of patients admitted to ICU. Methods A multidisciplinary group of 16 specialists in infectious disease, microbiology, pharmacology, and intensive care elaborated an expert opinion document through a multi-step approach: (1) the scientific panel defined the items and wrote the statements on the management of IFI in ICU, (2) a survey was submitted to an external panel to express agreement or disagreement on the statements, and (3) the panel reviewed the survey and implemented the final document. Results The final document included 35 statements that focused on epidemiology and microbiological rationale of the use of systemic L-AmB in critically ill patients and its potential role in specific clinical scenarios in the ICU. Conclusion Systemic L-AmB may represent an appropriate therapeutic choice for IFI in ICU patients with different underlying conditions, especially when the use of first-line agents is undermined. This expert opinion paper may provide a useful guide for clinicians.